2005
DOI: 10.1111/j.1523-1755.2005.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Serial crystalluria determination and the risk of recurrence in calcium stone formers

Abstract: These data provide evidence that crystalluria, when repeatedly found in early morning urine samples, is highly predictive of the risk of stone recurrence in calcium stone formers. Serial search for crystalluria, a simple and cheap method, may be proposed as a useful tool for the monitoring of calcium stone formers, in addition to urine biochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 44 publications
0
59
0
4
Order By: Relevance
“…As shown in Figure 2A, 1160 cm −1 was attributed to the O−P−O symmetric stretching vibration and 1080 cm -1 was attributed to the PO 4 3− asymmetric vibration absorption peak. As shown in Figure 2C, 989 cm −1 was attributed to the PO 4 3− symmetric vibration absorption peak.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As shown in Figure 2A, 1160 cm −1 was attributed to the O−P−O symmetric stretching vibration and 1080 cm -1 was attributed to the PO 4 3− asymmetric vibration absorption peak. As shown in Figure 2C, 989 cm −1 was attributed to the PO 4 3− symmetric vibration absorption peak.…”
Section: Resultsmentioning
confidence: 97%
“…[1][2][3] Therefore, the crystallites in urine are crucial factors affecting the formation of uroliths. [4][5][6] Previous studies 5,6 have found differences between the urinary crystallites (,1000 nm in size) of patients with urolithiasis and healthy subjects without any urolithiasis history. These studies concluded that the morphology, particle size, aggregation, and crystal phase of nanocrystallites in the urine of lithogenic patients remarkably differ from those of healthy persons.…”
Section: Introductionmentioning
confidence: 99%
“…De hecho se propone que un índice de cristaluria mayor a 0,5, definido como la relación del número de cristalurias positivas y el número total de muestras analizadas es indicador de un proceso de cristalización activa que conlleva un mayor riesgo de (5,11,25) recidivas . Al analizar los resultados de cristalurias de control observamos que una paciente presentó cristalurias positivas persistentes aun cuando después de iniciado tratamiento.…”
Section: Discussionunclassified
“…Otros tipos son independientes del pH y menos frecuentes como: 2,8-dihidroxi-adenina, cistina, xantina, tirosina, leucina e incluso medicamentos. Las cristalurias de origen medicamentoso suelen originarse como consecuencia (5)(6)(7) de dosis elevadas de los mismos .…”
Section: Introductionunclassified
“…Daudon [7] detected crystallites in morning urine samples, along with full 24-hour urine biochemical characteristics, in 181 patients with idiopathic calcium nephrolithiasis; in these cases, urinary crystallites were detected at a higher rate in the morning urine of 72 cases of patients than in full 24-hour urine. [8].…”
Section: Introductionmentioning
confidence: 99%